PET Radiotracers for Imaging P‐glycoprotein: The Challenge for Early Diagnosis in AD. Issue 1 (31st October 2013) - Leopoldo, Marcello; Contino, Marialessandra; Berardi, Francesco; Perrone, Roberto; Colabufo, Nicola Antonio
Abstract PET radiotracer development to target in vivo P‐glycoprotein (P‐gp) could be an important strategy for the early diagnosis of neurodegenerative disorders such as Alzheimer's disease (AD). Indeed, as a dysfunction of P‐gp is responsible for the accumulation of β‐amyloid plaques (a hallmark of AD) in brain parenchyma, P‐gp is the cause of AD onset. P‐gp substrates and inhibitors are useful for imaging the activity or expression of this protein, respectively; herein we discuss the in vivo evaluation of some 11C radiotracers with P‐gp‐inhibitory activity, such as [11C]MC18 and [11C]MC113, as well as P‐gp substrates [11C]MC266 and [11C]MC80. Moreover, the radiosynthesis of all these P‐gp probes is reported.